A case of Arrhythmogenic right ventricular cardiomyopathy without arrhythmias - Wei Jia; Tang Jiarong; Xia Liming; Chen Xinshan; Wang Dao (BMC, 2012)
Abstract Arrhythmogenic right ventricular cardiomyopathy (ARVC) is characterized by recurrent coma, ventricular tachycardias and the replacement of the myocardium with fatty and fibrous tissue. We described a 42-year-old female patient without clinical arrhythmias which was diagnosed as ARVC by magnetic resonance imaging (MRI), but the transvenous endomyocardial biopsy was not specific. The patient received heart transplantation due to her refractory heart failure and the pathology of explanted heart demonstrated typical replacement of fatty and fibrous tissue and piles of infiltrated lymphocytes in myocardial tissue. It is concluded that ARVC might not have any arrhythmias and inflammatory process may be involved in the mechanism of ARVC. Virtual slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/6573514507145351